Penerapan Model Pembelajaran Inkuiri Terbimbing Dalam Mata Pelajaran Dasar Desain Grafis Bagi Peserta Didik Nagarawangi - Sulidar Fitri; Sudirman Sudirman (JUPE : Jurnal Pendidikan Mandala, 2022)
Creativity is important in learning. sometimes in a learning process, teachers often pay less attention to the importance of students' creativity, this has an impact on decreasing students' creativity in doing assignments. The research method used is a quasi-experimental method using a pretest and posttest control group design. The population in this study were all students of class X Multimedia in the Nagarawangi village area. The technique of producing the sample in this study uses convenience sampling, the sample in this study consists of 20 participants then divided into 2 groups and the experimental method is 10 students in the experimental class and 10 other students in the control class. Based on the results of research and data analysis using the Man Whitney test in the experimental class and control class shows that the value of asymp.sig (2 tailed) is 0.00, which means H0 is rejected and H1 is accepted. This means that there are differences in the increase in creativity of students who use the Guided Inquiry learning model with the conventional model. The average increase in the experimental class is 0.80 and the control class is 0.10.